Application of Active Learning MIKiR Based on Critical Thinking in Improving Ability to Write Text Reports on Observations in Class VIII Students of SMP N 24 Jambi - Zhakia Drajat; Suwardi, Imam; Priyanto, Priyanto (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
Based on the researchers' observations during the observation at SMPN 24 Jambi City, when students were studying the text of the observation report, the teacher only gave the lecture method / used the conventional method and then the students did the assignment according to the contents of the text of the observation report they read, but there were still students who do not understand the contents of the text, because the text is too long so students become unfocused. Therefore the researcher offers a learning media approach in the form of critical thinking-based MIKiR media that can be used by teachers in learning observational report texts. The purpose of this study was to apply MIKiR learning media based on critical thinking as a learning medium for the text of observation reports in class VIII SMPN 24 Jambi City. The research was conducted at SMPN 24 Jambi City, the subjects of this study were Grade VIII students. The approach in this research is a quantitative approach. This type of research, descriptive. The data obtained is in the form of student work in the application of critical thinking-based MIKir media as a learning medium. The results showed that the application of critical thinking-based MIKiR active learning as a learning medium for the text material of observation reports for class VIII SMPN 24 Jambi City in its implementation was in accordance with the learning implementation plan. Starting from the teacher carrying out preliminary activities, then in the core stages the teacher explains, asks questions and determines the results of student work to be made, the teacher helps students determine themes, determines schedules for collecting work results, in closing activities the teacher concludes the learning that has been carried out.